The Evolving Science and Treatment of Thrombosis - Vinall, Maria (MD Conference Express, 2010)
A number of promising new antithrombotic agents intended to prevent atherothrombotic events in patients with coronary artery disease (CAD) and atrial fibrillation are currently being investigated. This article discusses the progress that is being made with adenosine diphosphate (ADP) inhibitors, antithrombins and factor Xa inhibitors. Other topics include the the problem of stent thrombosis and possible solutions.